2018
DOI: 10.2147/jpr.s160847
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain and geriatric syndromes in community-dwelling patients aged ≥65 years

Abstract: BackgroundIn growing elderly populations, there is a heavy burden of comorbidity and a high rate of geriatric syndromes (GS) including chronic pain.PurposeTo assess the prevalence of chronic pain among individuals aged ≥65 years in the Southern District of Israel and to evaluate associations between chronic pain and other GS.MethodsA telephone interview was conducted on a sample of older adults who live in the community. The interview included the Brief Pain Inventory and a questionnaire on common geriatric pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 49 publications
2
18
0
1
Order By: Relevance
“…Depression can lead patients to a negative and pessimistic perception and can have a negative effect on the patient's capacity to cope with pain (37,38). In neurobiologic terms, the main noradrenergic and serotonergic nuclei in the central nervous system are responsible for the chronicity of pain and development of depression (39). Actually, the result we obtained from regression analysis might be affected from examining depression with only one simple question.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Depression can lead patients to a negative and pessimistic perception and can have a negative effect on the patient's capacity to cope with pain (37,38). In neurobiologic terms, the main noradrenergic and serotonergic nuclei in the central nervous system are responsible for the chronicity of pain and development of depression (39). Actually, the result we obtained from regression analysis might be affected from examining depression with only one simple question.…”
Section: Discussionmentioning
confidence: 97%
“…In the definition of chronic pain, authors have used various durations of painful sensation, including pain longer than 3 months, 6 months or more (1). The prevalance of chronic pain in the adult population ranges from 20% to 50%, depending on the study population, the definition of "chronicity" and the definiton of the site of pain (2). Researches consistently show the prevalence of pain rising to a peak of 30-65% in the age group of 55-65 years and then declining somewhat to around 25-55% among those aged 85 years or over (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are some studies in the international literature that examine the relationships of pain and insomnia with falls among community‐dwelling older adults, no study has been performed in Turkey according to our knowledge. Moreover, the relationships of both pain and insomnia with falls were evaluated in this study based on the view that geriatric syndromes affect each other and have to be addressed together for effective management (Ates‐Bulut et al, 2018; Eyigör, ; Kaya et al, ; Liang et al, ; Liberman et al, ). In this study, pain was identified as a significant risk factor for falls among community‐dwelling older adults, with absence of pain considered as protective.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, sleep quality and pain are remediable risk factors that need attention. Pain and falls are commonly evaluated in studies of geriatric syndromes—clusters of unique features of common health conditions in elderly people (Ates‐Bulut, Soysal, & Isik, ; Liang, Rausch, Laflamme, & Möller, ; Liberman, Freud, Peleg, Keren, & Press, ; Thapa, Shmerling, Bean, Cai, & Leveille, ), and some recent studies have also assessed insomnia in this context (Eyigör, ; Kaya, Koçyiğit, Dokuzlar, Soysal, & Işık, ; Liang et al, ). Pain, insomnia, and falls, which are evaluated within the context of geriatric syndromes, are syndromes that negatively affect the quality of life of older adults and cause qualitative and quantitative deficiencies in daily activities and social relationships (Eyigör, ; Kaya et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation